Management of information systems in schools Under the Sisaket -Yasothon Secondary Education Service Area Office - Srangsok, Suphakiat; Phrompui, Chutima; Romsri, Suwattanapong (Journal of Research and Development Institute Rajabhat Maha Sarakham University, 2022)
The research purposes were: to study information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, and to compare of information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, classified by school size and working experience. The population was the teachers responsible for information system work under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, academic year 2020. The sample size was 83 teachers. The research instrument was the 5-estimate rating scale questionnaire, with the reliability level 0.84, inquired about the problems of information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon according to the guidelines for managing information systems within schools of Bureau of Educational Testing, Office of the Basic Education Commission include the data collection aspect, the data validation aspect, the data processing aspect, the data and information presentation aspect, the data and information storage aspect. The basic statistics for data analysis were the frequency, percentage, mean, and standard deviation; the hypothesis test statistics was the F-test. The research findings were: 1. Information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, overview was at high level. When each aspect consideration found the every aspect of problems of information system management in schools was at high level, the mean descending rank include the data collection aspect, the data validation aspect, the data and information storage aspect, the data and information presentation aspect, and the least was the data processing aspect. 2. The comparison results of information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, classified by school size and working experience found the opinion to problems of information system management in schools under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, overview and every aspect did not different.